Climbing the gap: a review on sex differences in high-level rock climbing - Langer, K.; Roffler, A.; Hief, P.; Fleddermann, M.-T. (Frontiers in Sports and Active Living, 2025)
Since its inclusion in the Olympic Program in 2016, climbing has grown increasingly popular and professionalized. While climbing research is also increasing, female (elite) athletes remain underrepresented, with the extent of this gap remaining unexplored. Therefore, the aims of this review are to (1) systematically review the published research in climbing, focusing on the inclusion of female athletes, (2) evaluate the differences between male and female climbers, and (3) formulate recommendations for future research and practice. A systematic literature search was performed in four databases in July 2025. In a general analysis, all included studies were analyzed regarding the representation of female participants. Peer-reviewed original studies assessing various factors of climbing performance in advanced to higher-elite climbers (speed, lead, and boulder—IRCRA minimum of 15 females and 18 males) were included. In a detailed analysis, studies specifically assessing sex-specific differences were categorized and analyzed with respect to these differences. A total of 246 met the inclusion criteria and were included in the general analysis. The results showed that studies in high-level climbing predominantly focus on male participants, both in terms of study design, with much more studies investigating isolated male athletes compared to females, and in participant distribution with only 22.7% female participants compared to male participants (66.5%). In addition, only 34 studies including sex-specific analyses were identified. The results demonstrate that male and female performance in the various climbing disciplines depend on different factors to varying degrees and reveal further important differences between male and female athletes. Our findings emphasize the need for future climbing research to focus on female athletes and further investigate sex-specific differences. Based on our findings, we propose recommendations to guide future research and practice.